Caffeine and attentional control: improved and impaired performance in healthy older adults and Parkinson’s disease according to task demands - Kanch Sharma; Sean James Fallon; Thomas Davis; Scott Ankrett; Greg Munro; Gary Christopher; Elizabeth Coulthard (Psychopharmacology, 2022)
Introduction Caffeine is frequently consumed to boost goal-directed attention. These procognitive effects may occur due to the adenosine-mediated enhancement of monoamines, such as dopamine, after caffeine administration. As such, caffeine’s beneficial effects may be altered in conditions such as Parkinson’s disease (PD). However, whether caffeine improves cognition, and at what cost, has not been experimentally established in patients with neurodegenerative disease. Methods Single-dose trials to probe cognitive effects of caffeine are often confounded by short-term caffeine abstinence which conflates caffeine’s effects with treatment of withdrawal. Using a placebo controlled, blinded, randomised trial design, we assessed the effect of 100 mg of caffeine across well-established tasks (Choice reaction time, Stroop Task and Rapid Serial Visual Presentation Task; RSVP) that probe different aspects of attention in PD patients ( n = 24) and controls ( n = 44). Critically, participants withdrew from caffeine for a week prior to testing to eliminate the possibility that withdrawal reversal explained any cognitive benefit. Results Caffeine administration was found to reduce the overall number of errors in patients and controls on the Stroop ( p = .018, η 2 p = .086) and Choice reaction time ( p < . 0001, η 2 p = .588) tasks, but there was no specific effect of caffeine on ignoring irrelevant information in the Stroop task. On the RSVP task, caffeine improved dual item accuracy ( p = .037) but impaired single item accuracy ( p = .044). Across all tasks, there was little evidence that caffeine has different effects in PD participants and controls. Conclusion When removing withdrawal effects as a factor, we demonstrate caffeine has beneficial effects on selective attention but is a double-edge sword for visual temporal attention and would need careful targeting to be clinically useful.

Deciphering sedimentary organic matter sources: Insights from radiocarbon measurements and NMR spectroscopy - Jonathan Sanderman; Evelyn Krull; Thomas Kuhn; Gary Hancock; Janine McGowan; Todd Maddern; Stewart Fallon; Andy Steven (Limnology and Oceanography, 2015)
In a sediment core collected from an estuary in a rapidly urbanizing region in South East Queensland, Australia, we used multiple geochemical tracers to understand the provenance, form, and rate of accumulating organic matter (OM) focusing on the application of two tools often used in studies of soil OM: solid‐state 13 C nuclear magnetic resonance (NMR) spectroscopy and interpretation of radiocarbon ( 14 C) data by modeling the uptake of the bomb‐spike in atmospheric 14 C. While elemental (C, N) and stable isotope ( 13 C, 15 N) data generally could not distinguish OM sources, these data did indicate that there has been a steady increase in nutrient loading to the estuary and that there were periodic deposition events where the OM was dominated by C3 terrestrial vegetation. The NMR results showed that the OM was primarily of terrestrial origin being dominated by lignin and stable char‐like carbon compounds in all samples. The 14 C data and modeling indicated that the OM was composed of a mixture of material with widely varying ages. In general, the OM was hundreds of years older than the age of the sediments as determined by fallout radionuclide dating (1950–2009 chronology), indicating that a large fraction of the OM has resided on the terrestrial landscape for a substantial period before being transported and buried in the estuary sediments. By applying this combination of techniques, we have been able to develop a coherent picture of a very complex deposition and accumulation history in these estuary sediments.

Geostatistical Simulation of Acoustic Log Data for Seismic Depth Conversion - Vanessa Cerqueira Koppe; João Felipe Coimbra Leite Costa; Jair Carlos Koppe; Fernando Gambin; Gary Fallon; Nick Davies (Natural Resources Research, 2007)

The Asymmetric Imino-aldol Approach to the Enantioselective Synthesis of β-amino acids - Marie-Isabel Aguilar; Gary D. Fallon; Penelpe A. Mayes; Sofia Nordin Andrea J. Robinson; Mark L. Rose; Filisaty Vounatsos; Bradley Wilman; Patrick Perlmutter (International Journal of Peptide Research and Therapeutics, 2003)